Intraspecific divergence in seedling trees of Persian walnut (Jugland regia) for metric tree, foliage and floral characters in Himachal Pradesh, India - Sharma, O.C.=700 1 Sharma, S.D.
(Es, En, Fr)
ilus., 17 ref.
Keywords: JUGLANS REGIA; VARIACION GENETICA; INDIA; NOGAL